Digital Democracy in the Era of TikTok: An Analysis of Social Media's Influence on Contemporary Political and Social Dynamics - Habibi, Muhammad (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This study examines the role of TikTok in digital democracy, particularly its impact on political and social dynamics. Using a descriptive qualitative method, the study analyzes how TikTok, through features like the "for your page" algorithm and two-way interactions, influences the spread of political information and the formation of public opinion. Through literature reviews, interviews with experts, and content analysis of TikTok, this research highlights how the platform can be used for political and radical propaganda, as well as how it addresses content oversight issues. The findings indicate both opportunities and challenges in using social media for politics, offering recommendations for digital media literacy and strategies to confront disinformation, and contribute to the understanding of the interaction between technology, politics, and society in an evolving context.